The Role Of Women In Science Reform And Their Scientific Activity - Khurshida Tokhirovna Komilova (Zien Journals, 2024)
The article examines the education of women in the field of science and their contribution to science, the activities of women in various fields of science. This paper examines the historical evolution of women’s participation in science, emphasizing the substantial obstacles they have surmounted and the prospects for future growth via the implementation of gender equality programs. The results of the research aimed at determining the characteristics of the social image of women in the field of science in Uzbekistan are highlighted
Keywords: education; science; women; field